Exploring Students’ Perceptions of Podcasts’ Role as a Tool in Promoting Vocabulary Acquisition Case of Third-Year Students at the University of Mohamed Cherif Messaadia in Souk-Ahras - Mohamed MESSAOUDI (My University, 2025)
Abstract This study explored the perceptions and self-reported usage patterns of third-year students of English as a Foreign Language (EFL) regarding podcasts as a tool for vocabulary acquisition at the University of Mohamed Cherif Messaadia-Souk-Ahras. The research employed a descriptive design with a mixed-methods approach to gain a comprehensive understanding of the current situation. A questionnaire was administered to third-year EFL students selected via convenience sampling, supplemented by semi-structured interviews with a small volunteer subset for deeper qualitative insights. The investigation focused on students' listening habits, their perceived effectiveness of podcasts for learning vocabulary in context, motivational factors, preferred podcast types, ease of use, and the specific challenges encountered, such as speech speed, accents, and vocabulary density. Findings indicated that students frequently engaged with podcasts and found them interesting, enjoyable, and motivating compared to traditional methods. They disclosed as well that students face significant challenges, particularly concerning comprehension speed and unfamiliar accents, leading to a strong desire for transcripts. Students seemed to value the authentic language exposure and contextual learning podcasts provided but required strategies or more support to overcome comprehension hurdles. Further, this study provided valuable descriptive insights for educators seeking to integrate podcasts effectively into EFL vocabulary instruction by highlighting student perspectives on benefits and barriers within a specific academic context. ---------------- Résumé Cette étude a exploré les perceptions et les modèles d’utilisation auto-déclarés des étudiants en troisième année de l’anglais comme langue étrangère (EFL) concernant les podcasts comme outil d’acquisition du vocabulaire à l’Université de Mohamed Cherif Messaadia-Souk-Ahras. La recherche a utilisé un design descriptif avec une approche à méthodes mixtes pour acquérir une compréhension globale de la situation actuelle. Un questionnaire a été administré aux étudiants de troisième année EFL sélectionnés via un échantillonnage de commodité, complété par des entretiens semi-structurés avec un petit sous-ensemble de volontaires pour des informations qualitatives plus approfondies. L’enquête s’est concentrée sur les habitudes d’écoute des étudiants, leur efficacité perçue des podcasts pour l’apprentissage du vocabulaire dans le contexte, les facteurs de motivation, les types de podcasts préférés, la facilité d’utilisation et les défis spécifiques rencontrés, tels que la vitesse de la parole, les accents et la densité du vocabulaire. Les résultats indiquent que les étudiants interagissent fréquemment avec les podcasts et les trouvent intéressants, agréables et motivants par rapport aux méthodes traditionnelles. Ils ont également révélé que les étudiants font face à des défis importants, en particulier concernant la vitesse de compréhension et les accents inconnus, ce qui conduit à un fort désir pour les relevés de notes. Les étudiants semblaient apprécier l’exposition linguistique authentique et les podcasts d’apprentissage contextuel fournis, mais nécessitaient des stratégies ou plus de soutien pour surmonter les obstacles à la compréhension. De plus, cette étude a fourni des informations descriptives précieuses pour les éducateurs cherchant à intégrer efficacement les podcasts dans l’enseignement du vocabulaire EFL en mettant en évidence les perspectives des étudiants sur les avantages et les obstacles dans un contexte académique spécifique.
Keywords: perceptions; podcasts; vocabulary acquisition; speech speed; unfamiliar accents: perceptions; podcasts; acquisition de vocabulaire; vitesse de la parole; accents inconnus